PELAKSANAAN KULIAH KERJA NYATA (KKN) DI DESA SUNGAI PANANGAH ANGKATAN XXIII KECAMATAN DANAU PANGGANGKABUPATEN HULU SUNGAI UTARA - Riska Riska; Yuhana Fauziah, Irma Hayatunnufus,Siti Fatimah, Muhammad Effendi, Muhammad Rayyan, Ahmad Syauki, Sit (JOURNAL OF COMMUNITY DEDICATION, 2021)
Real work lecture activities for STAI Rakha Amuntai students are a moment for students to forge themselves to live in society, an opportunity to practice knowledge and skills as well as an opportunity to add life provisions from the potential of the community that is the location of service. This research is a qualitative field research with a phenomenological approach. A phenomenological approach is used to analyze the phenomenon of the implementation of KKN in Sungai Panangah Village, Danau Panggang District. Data collection techniques used are observation, interviews, and documentation. Data processing and analysis techniques are through data reduction, data presentation, and verification or drawing conclusions. The results of the Real Work Lecture (KKN) in Sungai Panangah Village, Danau Panggang Subdistrict, are: First, the condition of Sungai Panangah Village is classified as lowland and the population is mostly farmers. Both organization and village administration are well organized. The three communities are religious, because of the many religious activities such as religious services, Yasinan, Maulid Habsy, Burdahan, Dalail and so on. The four STAI RAKHA Amuntai KKN in Sungai Panangah Village went well and smoothly and were able to examine and solve community problems across sectors, assist the government in achieving development and prepare cadres in rural areas by placing religion as the basis and guideline for driving and driving community activities